2022
DOI: 10.1007/s10620-022-07432-9
|View full text |Cite
|
Sign up to set email alerts
|

Unsedated Transnasal Endoscopy: A Safe, Well-Tolerated and Accurate Alternative to Standard Diagnostic Peroral Endoscopy

Abstract: Diagnostic unsedated transnasal endoscopy (uTNE) has been proven to be a safe and well-tolerated procedure. Although its utilization in the United Kingdom (UK) is increasing, it is currently available in only a few centers. Through consideration of recent studies, we aimed to perform an updated review of the technological advances in uTNE, consider their impact on diagnostic accuracy, and to determine the role of uTNE in the COVID-19 era. Current literature has shown that the diagnostic accuracy of uTNE for id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…Existing literature has previously demonstrated that TNE is a comparable alternative to c-OGD as a diagnostic modality for numerous GI pathologies 5. Here, the inlet patch detection, a proposed surrogate of endoscopic quality, was 5.7% and comparable with the background rate from c-OGD,15 which suggests a similar degree of mucosal inspection quality.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Existing literature has previously demonstrated that TNE is a comparable alternative to c-OGD as a diagnostic modality for numerous GI pathologies 5. Here, the inlet patch detection, a proposed surrogate of endoscopic quality, was 5.7% and comparable with the background rate from c-OGD,15 which suggests a similar degree of mucosal inspection quality.…”
Section: Discussionsupporting
confidence: 63%
“…Transnasal endoscopy (TNE) uses an ultra-thin endoscope of less than 6 mm diameter via the nasal route and is typically performed with the patient sitting upright. This offers an elegant solution to several problems facing endoscopy services in the post-COVID-19 era 5. As an unsedated procedure that bypasses the tongue, palate and uvula, TNE minimises stimulation of the gag reflex6 and offers excellent patient tolerability while the absence of sedation is cost-saving in terms of equipment, monitoring, and nursing resources during and after the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the benefits of this strategy in all scenarios should not be entirely assumed, especially for high-tech less invasive tests that require intense manufacturing and processing. Until further data are available, ESGE-ESGENA encourage less invasive tests for the indications endorsed by evidence-based clinical guidelines (▶ Table 4 [48][49][50][51][52][53][54][55][56]).…”
Section: Statementmentioning
confidence: 99%
“…Transnasal endoscopy results in less pain without the use of sedatives as it induces the gag re ex to a lesser extent than peroral endoscopy with a normal-diameter endoscope (3)(4)(5)(6)(7)(8)(9)(10)(11). A suppressed gag re ex is useful during the Coronavirus disease-19 pandemic as it limits the spread of infection via airborne droplets (12). In addition, transnasal endoscopy does not signi cantly affect the patient's hemodynamics, minimizing the burden on the patient (13)(14).…”
Section: Introductionmentioning
confidence: 99%